Hippocampal Subfield Volumes: Age, Vascular Risk, and Correlation with Associative Memory - Shing, Yee Lee; Rodrigue, Karen M.; Kennedy, Kristen M.; Fandakova, Yana; Bodammer, Nils; Werkle-Bergner, Markus; Lindenberger, Ulman; Raz, Naftali (Frontiers in Aging Neuroscience, 2011)
Aging and age-related diseases have negative impact on the hippocampus (HC), which is crucial for such age-sensitive functions as memory formation, maintenance, and retrieval. We examined age differences in hippocampal subfield volumes in 10 younger and 19 older adults, and association of those volumes with memory performance in the older participants. We manually measured volumes of HC regions CA1 and CA2 (CA1-2), sectors CA3 and CA4 plus dentate gyrus (CA3-4/DG), subiculum and the entorhinal cortex using a contrast-optimized high-resolution PD-weighted MRI sequence. Although, as in previous reports, the volume of one region (CA1-2) was larger in the young, the difference was due to the presence of hypertensive subjects among the older adults. Among older participants, increased false alarm (FA) rate in an associative recognition memory task was linked to reduced CA3-4/DG volume. We discuss the role of the dentate gyrus in pattern separation and the formation of discrete memory representations.